Prospects for nasal delivery of a pharmacologic agent for neuroprotective experimental therapy after prenatal hypoxia - Belenichev, Igor; Aliyeva, Olena; Bukhtiyarova, Nina; Ryzhenko, Victor; Burlaka, Bogdan; Burlaka, Kristina; Skoryna, Dmytro; Petakh, Pavlo; Kamyshnyi, Oleksandr (Frontiers in Systems Neuroscience, 2025)
Prenatal hypoxia (PH) significantly impacts the central nervous system (CNS) development, often resulting in long-term cognitive, behavioral, and neurological deficits due to oxidative stress, mitochondrial dysfunction, and neuroapoptosis. The brain’s endogenous protective mechanisms are often insufficient under prolonged hypoxia, necessitating the development of novel neuroprotective strategies. This study aimed to evaluate the neuroprotective efficacy of nasal administration of Angiolin gel—a novel pharmacological agent—in experimental model of PH. Chronic intrauterine hypoxia was induced in pregnant rats via sodium nitrite administration. Newborn rats were divided into groups receiving either Angiolin gel intranasally, Piracetam intraperitoneally, or saline (control) for 30 days. Biochemical, morphometric, histoimmunochemical, and neurophysiological methods were employed to assess outcomes. The results demonstrated that PH induced mitochondrial dysfunction, oxidative and nitrosative stress, GABAergic system impairment, and neuroapoptosis, leading to increased neonatal mortality and deficits in cognitive and motor functions. Angiolin gel administration significantly enhanced energy metabolism by restoring mitochondrial enzyme activities (SDH, MDH, and CPK), increasing ATP production, and reducing lactate accumulation. It also normalized GABAergic parameters, increased the activity of antioxidant enzymes (Cu/Zn-SOD, GPX1/4) and decreased nitrosative stress markers (iNOS, nitrotyrosine). Histomorphometric analysis revealed preserved neuronal density and reduced apoptosis in the hippocampus, alongside enhanced Fos/Bcl-2 expression. Behavioral tests demonstrated improved motor activity, memory retention, and exploratory behavior, with a 47% reduction in early mortality. Comparative analysis showed superior efficacy of Angiolin over Piracetam, which exacerbated lactate acidosis. These findings suggest that intranasal administration of Angiolin gel effectively targets multiple pathophysiological pathways triggered by PH, providing robust neuroprotection and promoting functional recovery. Given its favorable safety profile and the non-invasive nature of intranasal delivery, Angiolin gel represents a promising therapeutic approach for mitigating the long-term neurological consequences of prenatal hypoxia and warrants further clinical investigation in neonatal and pediatric neurology.